Unsteady aerodynamics of high work turbines - Richardson, David (Cranfield University, 2009)
One method aircraft engine manufactures use to minimize engine cost and weight is to reduce the number of parts. A significant reduction includes reducing the turbine blade count or combining two moderately loaded turbines into one high-work turbine. The risk of High Cycle Fatigue in these configurations is increased by the additional aerodynamic forcing generated by the high blade loading and the nozzle trailing edge shocks. A lot of research has been done into the efficiency implications of supersonic shocks in these configurations. However what is less well understood is the resulting unsteady rotor forces. These unsteady aerodynamics aspects are the focus of this research. The research investigates where manufacturers might concentrate their resources to reduce Direct Operating Costs (DOC). It compares the relative financial implications of disruption events to the cost of reducing DOC by further efficiency gains. The technical aspects of the research use computational aerodynamic modelling of a high work turbine to explore the unsteady aerodynamics and the resulting rotor forces. Investigation of parametric models into the effect of reaction, axial spacing, pressure ratio, the nozzle wake profile and the significance of the rotor boundary layer in dissipating the high gradient shocks is also investigated. Data from an experimental test program was used to characterise sub- and super-critical shock boundary layer interactions to determine if they are a significant forcing function. The primary conclusions from this research include the relative merits of targeting resources into reducing disruption events rather than the relatively small financial gains which might be gained through further efficiency improvement by researching advanced technologies. The computational method is validated against an experimental dataset from a high-speed turbine stage rig. Overall, good agreement is found between the measurements and the predictions for both the detailed unsteady aerodynamics as well as the important rotor forces. The effect of different computational modelling standards is also explored. The relative significance of the primary aerodynamic forcing functions such as the nozzle wake and trailing edge shock system is evaluated. Generally the rotor forces are found to increase with lower reaction, reduced axial spacing and higher pressure ratio. However the phasing of the forcing functions is found to be a critical aspect in determining the resultant net unsteady forces. The sub-critical shock boundary layer interaction is determined to be a second order effect in relation to the other primary forcing mechanisms, however the supercritical shock boundary layer interaction is shown to be a potential contributory factor in rotor forcing. Finally, several recommendations are proposed which turbine designers should apply in the event that rotor forcing is considered to be a significant concern.